Ezetimibe Lipid-Lowering Trial on Prevention of Atherosclerotic Cardiovascular Disease in 75 or Older (EWTOPIA 75): A Randomized, Controlled Trial. Issue 12 (17th September 2019) - Ouchi, Yasuyoshi; Sasaki, Jun; Arai, Hidenori; Yokote, Koutaro; Harada, Kazumasa; Katayama, Yasuo; Urabe, Takao; Uchida, Yasufumi; Hayashi, Masaru; Yokota, Naoto; Nishida, Hirokazu; Otonari, Takatoshi; et al.
Abstract : Background: Evidence regarding the primary prevention of coronary artery disease events by low-density lipoprotein cholesterol (LDL-C) lowering therapy in older individuals, aged ≥75 years, is insufficient. This trial tested whether LDL-C–lowering therapy with ezetimibe is useful for the primary prevention of cardiovascular events in older patients. Methods: This multicenter, prospective, randomized, open-label, blinded end-point evaluation conducted at 363 medical institutions in Japan examined the preventive efficacy of ezetimibe for patients aged ≥75 years, with elevated LDL-C without history of coronary artery disease. Patients, who all received dietary counseling, were randomly assigned (1:1) to receive ezetimibe (10 mg once daily) versus usual care with randomization stratified by site, age, sex, and baseline LDL-C. The primary outcome was a composite of sudden cardiac death, myocardial infarction, coronary revascularization, or stroke. Results: Overall, 3796 patients were enrolled between May 2009 and December 2014, and 1898 each were randomly assigned to ezetimibe versus control. Median follow-up was 4.1 years. After exclusion of 182 ezetimibe patients and 203 control patients because of lack of appropriate informed consent and other protocol violations, 1716 (90.4%) and 1695 (89.3%) patients were included in the primary analysis, respectively. Ezetimibe reduced the incidence of the primary outcome (hazard ratio [HR], 0.66; 95% CI, 0.50–0.86; P =0.002). Regarding the secondary outcomes, the incidences of composite cardiac events (HR, 0.60; 95% CI, 0.37–0.98; P =0.039) and coronary revascularization (HR, 0.38; 95% CI, 0.18–0.79; P =0.007) were lower in the ezetimibe group than in the control group; however, there was no difference in the incidence of stroke, all-cause mortality, or adverse events between trial groups. Conclusions: LDL-C–lowering therapy with ezetimibe prevented cardiovascular events, suggesting the importance of LDL-C lowering for primary prevention in individuals aged ≥75 years with elevated LDL-C. Given the open-label nature of the trial, its premature termination and issues with follow-up, the magnitude of benefit observed should be interpreted with caution. Clinical Registration: URL: https://www.umin.ac.jp . Unique identifier: UMIN000001988. Abstract : Supplemental Digital Content is available in the text.